Makna Retoris Penggunaan Diksi Nahyi dalam Surah Al-Isra' (Analisis Ilmu Ma'ani) - Muhammad Alif Ramadhan; Haniah; Mohamad Harjum Harjum (Riyahuna: Jurnal Pendidikan Bahasa Arab, 2026)
ABSTRACT This study aims to analyze the rhetorical meanings of uslub nahyi (prohibitive expressions) in Surah Al-Isra’ through the perspective of علم المعاني (Ilmu Ma‘ani), with a focus on the selection of prohibitive diction and the semantic effects it produces. This research was conducted because uslub nahyi in the Qur’an does not merely function as a literal prohibition, but also contains rhetorical dimensions capable of shaping human moral, ethical, and psychological awareness. The study employs a qualitative approach using library research. The primary data consist of the verses containing uslub nahyi in Surah Al-Isra’, while the secondary data were obtained from books of balaghah, works on Ilmu Ma‘ani, and relevant Arabic linguistic literature. Data were collected through documentation study and analyzed descriptively and analytically by examining the context of the verses, sentence structures, and diction choices in each prohibitive form. The findings reveal that uslub nahyi in Surah Al-Isra’ carries various rhetorical meanings, such as irsyad (guidance), tahdid (threat), and taubikh (reproach). The study also finds that certain diction choices, such as “لَا تَقْرَبُوا” (“do not approach”), do not merely prohibit an act itself, but also all paths leading to it, thereby forming a preventive pattern of prohibition. The results of this study contribute to the development of Qur’anic rhetorical studies, particularly in understanding the relationship between diction selection, context, and the rhetorical purpose of the verses. The novelty of this research lies in its focus on the rhetorical dimension of diction selection in uslub nahyi within Surah Al-Isra’, rather than merely classifying its rhetorical meanings. Keywords : Uslub Nahyi, Surah Al-Isra’, Ilmu Ma‘ani, Rhetorical Meaning.